2001
DOI: 10.1136/adc.85.5.438
|View full text |Cite
|
Sign up to set email alerts
|

Use of cough swabs in a cystic fibrosis clinic

Abstract: We audited prospectively 322 cough swabs taken from cystic fibrosis children and compared cough swabs with concomitant sputum samples in 30 expectorating patients. A positive cough swab is a strong predictor of sputum culture. However, a negative cough swab does not rule out infection. Persistent symptoms should be further investigated. (Arch Dis Child 2001;85:438-439) Keywords: cystic fibrosis; cough swabs; sputum; clinic Over the past two decades survival has improved in cystic fibrosis (CF), mainly as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 6 publications
4
40
0
2
Order By: Relevance
“…However these samples poorly reflect the presence of organisms deeper in the respiratory tract and a negative cough swab does not rule out infection [12]. The use of qPCR on cough swabs as well as sputa allowed a significant improvement in the detection of P. aeruginosa over routine bacteriological culture.…”
Section: Discussionmentioning
confidence: 96%
“…However these samples poorly reflect the presence of organisms deeper in the respiratory tract and a negative cough swab does not rule out infection [12]. The use of qPCR on cough swabs as well as sputa allowed a significant improvement in the detection of P. aeruginosa over routine bacteriological culture.…”
Section: Discussionmentioning
confidence: 96%
“…However, these methods have been shown to have variable diagnostic accuracy when compared to BAL [6][7][8] or expectorated sputum [9][10][11]. Furthermore, common CF pathogens are present in the upper airways of healthy children [12,13], further complicating meaningful interpretations of positive upper airway bacterial cultures.…”
Section: Introductionmentioning
confidence: 93%
“…In our study and the Brompton study 4 cough swabs were taken in an outpatient setting, using a method involving no direct contact with the oropharynx. The Brompton study 4 showed that cough swabs compared with sputum samples had a specificity of 100% but sensitivity of 34%. Our study showed a comparable sensitivity of 35%.…”
Section: Discussionmentioning
confidence: 99%